The Influence of Health level, Education level and The amount of poor Society Toward Economic Growth in West Sumatera - Rahmawati, Eka; Maryati, Sri; Eka Putri, Yosi (Pendidikan Ekonomi, 2014)
ABSTRACTÂ The purpose of this research is to analysis influence of health level variable, education level andthe amount of poor society toward economic growth in province West Sumatera. Type of research that was used in this research is inductive research. The data was used in this research is secundery data at 1997-2011 years. The data was collected through publication of library research or bibliography by âBadan Pusat Statistikâ West Sumatera.The tool to analysis the data in this research is econometrica approach with used mltiple regression equation with double log equation. In partial test the result of this research sowed that health level variable and education level have positive influence and significance to economic growth in West Sumatera., whereas the amount of poor society did not have influence to economic growth in simultance the healt level variable, education variable and sum of poor society ave significance influence to economic growth in West Sumatera.From result of the study was concluded that Economic Growth in West Sumatera can urge on increase âStandar Minimal Pendidikan (SPM) and increased society realize with importance of health to increased economic growth in West Sumatera.Key word: Health Level, Education Level, the amount of Poor Society and Economic GrowthÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Penelitian ini bertujuan untuk menganalisis pengaruh variabel tingkat kesehatan, tingkat pendidikan dan jumlah penduduk miskin terhadap pertumbuhan ekonomi di Provinsi Sumatera Barat. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian induktif. Adapun data yang di gunakan dalam penelitian ini adalah data sekunder tahun 1997 sampai tahun 2011.Data dikumpulkan melalui riset pustakaan merupakan publikasi atau dibukukan oleh Badan Pusat Statistik Sumatera Barat.Alat analisa data dalam penelitian in adalah pendekatan ekonometrika dengan menggunakan persamaan regresi berganda dengan persamaan double log.Secara parsial hasil penelitian menunjukkan bahwa variabel tingkat kesehatan dan tingkat pendidikan berpengaruh positif dan signifikan terhadap pertumbuhan ekonmi Sumatera Barat, sedangkan jumlah penduduk miskin tidak berpengaruh terhadap pertumbuhan ekonomi.secara simultan variabel tingkat kesehatan, tingkat pendidikan dan jumlah penduduk miskin berpengaruh signifikan terhadap pertumbuhan ekonomi di Sumatera Barat.Dari hasil studi disimpulkan bahwa Pertumbuhan Ekonomi di Sumatera Barat dapat di dorong dengan meningkatkanÂ Standar Minimal Pendidikan(SPM) dan meningkatkan kesadaran masyarakat akan pentingnya kesehatan guna meningkatkan pertumbuhan ekonomi di Sumatera Barat.Kata kunci: Tingkat Kesehatan, Tingkat Pendidikan, Jumlah Penduduk Miskin dan Pertumbuhan EkonomiÂ